ID: 213. Issue 1 (November 2015) - Mahlakoiv, Tanel; Hernandez, Pedro; Diefenbach, Andreas; Staeheli, Peter
<x xml:space="preserve">Abstract</x> The epithelium is the main entry point for many viruses, but the processes that protect barrier surfaces against viral infections are incompletely understood. Here we identified interleukin 22 (IL-22) produced by innate lymphoid cell group 3 (ILC3) as an amplifier of signaling via interferon-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7r42" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />λ</alternatives> (IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rbc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />λ)</alternatives>, a synergism needed to curtail the replication of rotavirus, the leading cause of childhood gastroenteritis. Cooperation between the receptor for IL-22 and the receptor for IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7r42" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />λ</alternatives>, both of which were 'preferentially' expressed by intestinal epithelial cells (IECs), was required for optimal activation of the transcription factor STAT1 and expression of interferon-stimulated genes (ISGs). These data suggested that epithelial cells are protected against viral replication by co-option of two evolutionarily related cytokine networks. These data may inform the design of novel immunotherapy for viral infections that are sensitive to interferons.